1980
DOI: 10.1177/002383098002300106
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception

Abstract: The paper reviews selected studies in speech perception, most of them published in the past five years. Topics include the contributions of prosody to segmental perception, the problems of segmentation and invariance, categorical perception of speech and non-speech, the role of feature detectors, the scaling of speech sounds to an auditory-articulatory space, acoustic phonetic dependencies within the syllable, the contributions of higher order (nonphonetic) factors to the comprehension of fluent speech, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 93 publications
0
23
0
1
Order By: Relevance
“…Perception requires no arbitrary association of signal with phone-tic category, and no correspondingly arbitrary progression from an auditory stage (e.g., different sounding glissandi) to a superseding phonetic label. As Studdert-Kennedy (1976) has put it, the phonetic category 'names itself'.…”
Section: The Account Provided By the Motor Theorymentioning
confidence: 99%
“…Perception requires no arbitrary association of signal with phone-tic category, and no correspondingly arbitrary progression from an auditory stage (e.g., different sounding glissandi) to a superseding phonetic label. As Studdert-Kennedy (1976) has put it, the phonetic category 'names itself'.…”
Section: The Account Provided By the Motor Theorymentioning
confidence: 99%
“…Nevertheless, more meticulous spectral analysis reveals that each short segment of speech carries information on one phoneme together with its bordering phonemes (A. M. Liberman, 1970aLiberman, , 1970bA. M. Liberman, Cooper, Shankweiler, & Studdert-Kennedy, 1967;Massaro, 1975;Studdert-Kennedy, 1975). For example, what one could isolate as the spectral representation of the phoneme /s/ appears to differ in the syllables /su/ and lsi!…”
Section: The Natural Confounding Of Time and Informationmentioning
confidence: 99%
“…For instance, Remington (1977) demonstrated that in a CVC syllable, although the initial consonant precedes the vowel, recognition of the vowel can occur before recognition ofthe initial consonant. Even though this reversal is not due so much to the functioning ofauditory memory as to the way speech sounds are coarticulated (see Studdert-Kennedy, 1975, for a review), it suggests that the phenomenological experience of the temporal deployment of speech and the actual reality can sometimes show important discrepancies.…”
Section: Wrong Start: the Need For Backtracking And For A Processing mentioning
confidence: 99%
“…In this section we review thes two aspects of whet has been learned about the problem. (StUddert-Kennedy, 1976), among others as basic unite In perceon. RegardIess of which of these propol one favors, It nonetheless seems clear that at various levels of processing there exist sown kind~s) of wit which have been extracted from the speech signal (lis conclusion appears necessary If one assume a generative capacity I speech percept) it is theirefor umuaily assumed that an Important and appropriate task for speech analysis Is somieliow to segment the speech input-to draw Hnes separating the The problem Is that whatever the units of perception are, thabk boundaries we rarely evident In the signal (Zue & Schwartz, 1980).…”
Section: Interactive Activation In Speech Perceptionmentioning
confidence: 99%